PENGARUH KOMISARIS INDEPENDEN DAN KEPEMILIKAN MANAJERIAL TERHADAP KINERJA KEUANGAN DENGAN KONSERVATISME AKUNTANSI SEBAGAI VARIABEL INTERVENING - Jaya, Ajun Daruri; Zulfikar, Rudi; Astuti, Kurniasih Dwi (EQUITY: Jurnal Ekonomi, Manajemen, Akuntansi, 2018)
This study aimed to analyze the influence of Independent Comission er and manajerial ownership on financial performance with accounting conservatism as an intervening variable. Independent Comissioner is m easured by total Independent Comissioner divided by total Independent Board, manajerial ownership is measured by share owned by mana jemen divided by total outstanding share, financial performance is proxied with Return On Asset and accounting conservatism is proxied by the Book to Market Ratio. The sample in this study are as many as 174 companies, and samples u sed in this study is a manufacturing company listed on the Indonesia Stock exchange during 2012-2016. The statistical method used is regression analysis with path analysis. The results show that better corporate governance, in terms of greater of independence commissioner and manajerial ownership shows to be a direct relation tofinancial performance. On the other hand , manajerial ownership lowered the financial performance via accounting conservatism. Howeever, in terms of greater independent commissioner does not lowered the financial performancce via accounting conservatism.